Genetic predictors of relapse rate in pediatric MS. (October 2016) - Graves, Jennifer S; Barcellos, Lisa F; Shao, Xiaorong; Noble, Janelle; Mowry, Ellen M; Quach, Hong; Belman, Anita; Casper, T. Charles; Krupp, Lauren B; Waubant, Emmanuelle; ,
Background: Genetic ancestry, sex, and individual alleles have been associated with multiple sclerosis (MS) susceptibility. Objective: To determine whether established risk factors for disease onset are associated with relapse rate in pediatric MS. Methods: Whole-genome genotyping was performed for 181 MS or high-risk clinically isolated syndrome patients from two pediatric MS centers. Relapses and disease-modifying therapies were recorded as part of continued follow-up. Participants were characterized for 25-hydroxyvitamin D serum status. Ancestral estimates (STRUCTURE v2.3.1), human leukocyte antigen ( HLA ) -DRB1*15 carrier status (direct sequencing), sex, and a genetic risk score (GRS) of 110 non-HLA susceptibility single-nucleotide polymorphisms (SNPs) were evaluated for association with relapse rate with Cox and negative binomial regression models. Results: Over 622 patient-years, 408 relapses were captured. Girls had greater relapse rate than boys (incident rate ratio (IRR) = 1.40, 95% confidence interval (CI) = 1.04–1.87, p = 0.026). Participants were genetically diverse; 40% ( N = 75) had <50% European ancestry. HLA-DRB1*15 status modified the association of vitamin D status ( p ixn = 0.022) with relapse rate (per 10 ng/mL, in DRB1*15 + hazard ratio (HR) = 0.72, 95% CI = 0.58–0.88, p = 0.002; in DRB1*15− HR = 0.96, 95% CI = 0.83–1.12, p = 0.64). Neither European ancestry nor GRS was associated with relapse rate. Conclusion: We demonstrate that HLA-DRB1*15 modifies the association of vitamin D status with relapse rate. Our findings emphasize the need to pursue disease-modifying effects of MS genes in the context of environmental factors.